Coupling diverse routes of calcium entry to mitochondrial dysfunction and glutamate excitotoxicity - Stanika, Ruslan I. (National Academy of Sciences, 2009)
Overactivation of NMDA receptors (NMDARs) is a critical early step in glutamate-evoked excitotoxic injury of CNS neurons. Distinct NMDAR-coupled pathways specified by, for example, receptor location or subunit composition seem to govern glutamate-induced excitotoxic death, but there is much uncertainty concerning the underlying mechanisms of pathway selection. Here we ask whether, and if so how, route-specific vulnerability is coupled to Ca(2+) overload and mitochondrial dysfunction, which is also a known, central component of exitotoxic injury. In cultured hippocampal neurons, overactivation of only extrasynaptic NMDARs resulted in Ca(2+) entry strong enough to promote Ca(2+) overload, which subsequently leads to mitochondrial dysfunction and cell death. Receptor composition per se appears not to be a primary factor for specifying signal coupling, as NR2B inhibition abolished Ca(2+) loading and was protective only in predominantly NR2B-expressing young neurons. In older neurons expressing comparable levels of NR2A- and NR2B-containing NMDARs, amelioration of Ca(2+) overload required the inhibition of extrasynaptic receptors containing both NR2 subunits. Prosurvival synaptic stimuli also evoked Ca(2+) entry through both N2A- and NR2B-containing NMDARs, but, in contrast to excitotoxic activation of extrasynaptic NMDARs, produced only low-amplitude cytoplasmic Ca(2+) spikes and modest, nondamaging mitochondrial Ca(2+) accumulation. The results—showing that the various routes of excitotoxic Ca(2+) entry converge on a common pathway involving Ca(2+) overload-induced mitochondrial dysfunction—reconcile and unify many aspects of the “route-specific” and “calcium load-dependent” views of exitotoxic injury.